Presenting numbers, tables, and charts - Bigwood, Sally (Oxford University Press, 2003)
A book of practical advice and useful tips on how to present numeric information in the clearest and most effective way. This lively, accessible, and illustrated guide is divided into two sections. The first provides comprehensive advice on what to consider when preparing numeric information for presentation, standards for presenting tables and graphs to the public, including the relative merits and uses of tables and charts, and the presentation of figures in both written and spoken form. The second section contains useful checklists, case studies, and exercises to aid the writer, as well as a helpful glossary